Adaptação de sistema de indicadores para avaliação da sustentabilidade da aldeia akrãti, povo indígena akrãtikatêjê - ARAÚJO, William Bruno Silva (2017)
The Akrãtikatêjê people as well as Parkatêjê and Kyikatêjê are generally known in the literature as "Gavião do Pará" and inhabit the Mãe Maria Indigenous Land, located in the municipality of Bom Jesus do Tocantins, Southeastern State of Pará. Nowadays, the Akrãtikatêjê have redesigned their strategies of involvement with nature in order to guarantee its perpetuation. These transformations-adaptations are materialized through the implementation of productive activities that they call "sustainable projects". On the other hand, they try to preserve their beliefs, traditional productive practices and worldviews. In this context, the research sought to understand these transformations in the light of sustainability. The research adopted perspective and qualitative treatment and was articulated through the Participatory Action Research (IAP). The Management System Assessment Framework Incorporating Indicators of Sustainability - MESMIS, a methodological tool guided by the systemic approach, transdisciplinarity and participation, was taken as a methodological tool. The Akrktikatêjê people can be considered an example of cultural and ethnoecological resistance, through cosmoethics, a relationship of care, respect and belonging-involvement with nature. As a result of the research, the indicators "Control and Surveillance Territory" and "Revitalization and strengthening of Culture" were developed, which can contribute to evaluate the current state of sustainability of the Akrãtikatêjê management system and to inform their future strategies